Tidal Breathing Pulmonary Function of Children With Allergic Rhinitis - Du, Hui; Liu, Xueru; Peng, Fang; Chen, Hebin; Wang, Yanli (Frontiers in Pediatrics, 2022)
In order to investigate the characteristics of tidal breathing pulmonary function in children with allergic rhinitis, and explore its role in the relationship between allergic rhinitis and asthma, we conducted this prospective study from January 4, 2016 to January 30, 2019 in Wuhan children’s hospital. In this study, 49 children with simple allergic rhinitis were enrolled in the AR group; 50 children with allergic rhinitis concomitant with asthma were enrolled in the AR&A group; 43 healthy children were recruited in the control group. For individuals in each group, the assessment of tidal breath pulmonary function was performed after enrollment. Then participants in the AR group and control group were followed up for 1 year to observe their frequency of wheezing attacks. The parameters of tI/tE, tPTEF/tE and VPTEF/VE of AR group were significantly higher than AR&A group (P<0.001). The reduced proportion of tPTEF/tE and VPTEF/VE. in AR group were higher than that in control group (30.61% vs. 11.63%, P<0.001; 24.49% vs. 11.63%, P<0.001, respectively). The proportion of patients with reduced tPTEF/tE and VPTEF/VE who occurred recurrent wheezing was higher than that of patients with normal pulmonary function in AR group(P=0.008). In conclusion, some children with allergic rhinitis has impaired tidal breathing pulmonary function. Tidal breathing pulmonary function test plays an important role in the diagnosis and assessment of children's airway allergic diseases (AR and asthma).